"A designer diet layout for astronauts using a microbiome mediated approach.". Issue 1 (8th June 2022) - Arora, Smriti; Puri, Samikshha; Bhambri, Nitika
Abstract: Astronauts undergo space travel to bring scientific information to benefit humanity under various missions of space agencies such as NASA, European Space Agency, Indian Space Research Organization etc. During space missions, they encounter several stressors namely microgravity, fluid shifts, cosmic radiation, sleep deprivation and alteration in the circadian rhythm perturbing the quality of sleep. In addition, confined spaces makes pathogen interaction more likely if a pathobiont gets introduced into spacecraft. Microbiota is the first line оf resistаnсe tо vаriоus disorders and diseаses. It direсtly influenсes the biосhemiсаl, рhysiоlоgiсаl, аnd immunоlоgiсаl раthwаys. 'Gut microbiota' is essential for maintenance of healthy gut barrier functions. 'Dysbiosis' refers to perturbation of microbiota which is correlated with several metabolic and psychological disorders. Microbial metabolites are implicated in maintenance of human health. Investigations conducted on astronauts in international space missions and on analog terrestrial models have indicated a 'dysbiosis' of the gut microbiota associated with spaceflights. 'Dysbiosis' of the gut microbiome observed in astronauts has been implicated in immune dysregulation and a probiotic enriched diet is proposed to restore immune homeostasis. This article not just summarizes the state of art research on dysbiosis of the gut microbiome of astronauts, but also a diet mediated correction plan to restore their health especially during long term space missions. A characterization of microbial metabolites of the gut to enable administration of astronaut specific probiotic, postbiotic or synbiotic to alleviate space associated dysbiosis is proposed. It is also recommended that astronauts maintain a balanced nutritious diet throughout life to promote a resilient microbiota that is not perturbed by space missions. Further, a bioregenerative life support system wherein a probiotic may be produced in space station is proposed. Abstract : Promoting astronaut's health in challenging space environments using special diet inclusive of pre and probiotics would allow astronauts to continue space missions with zeal and maintain their physical and emotional health.